Analisis Jumlah Welder dan Operator Welding Preparation yang Optimal untuk Mengurangi Bottleneck pada Proses Welding - Agnes Yosephine Kosasih; I Nyoman Sutapa (Jurnal Titra, 2018)
PT XYZ is a manufacturing company engaged in the manufacture of heat exchangers. PT XYZ has a make to order demand fulfillment strategy with large product variations. The existing production process at the company consists of several lines, one of which is the SS-CS line. SS-CS line has a bottleneck in one of the processes, which is welding process. The welding process itself is done by welder and welding preparation operator. The number of welders and welding preparation operators is considered unbalanced, causing a bottleneck in the welding process. The purpose of this research is to find the optimal number of welder and welding preparation operator so that the welding process no longer having bottleneck. The optimal number of welder through calculation result and simulation is 16 people while operator welding preparation is 7 people. The output produced with the optimal number of workers can reach more than 2 times the original condition. The average utility of both types of workers is over 90% and is almost balanced with a 5.98% difference. By implementing this proposal, the company can save Rp. 504,523.90 per month in terms of not needing anymore overtime costs that have been issued and the salary addition of workers to be issued.